RETHINKING VISIONS OF “UNITY” AND “BELONGING”: INSIGHTS INTO AUDIENCE RESPONSES TOWARDS POPULAR MUSIC OF MALAYSIA’S INDIGENOUS ETHNIC COMMUNITIES – A CASE OF IBAN POP SONG - Collin, Jerome; Ting, Su Hie; Esther John, Perry (Penerbit Universiti Sains Malaysia, 2022)
This article presents the findings of a larger ongoing study that explores visions of “unity” and “belonging” among present-day Malaysians that are shaped by their engagements with popular music genres of the country’s indigenous ethnic communities. Through a critical theory-informed qualitative analysis of Malaysians’ views on the popular Iban song, “Biar Bekikis Bulu Betis”, the study described in this article examines the visions of unity and belonging that they conceived through various engagements with the song. The findings show that these visions were co-created in and through a dynamic interaction between the song and the audience. The former evoked a sense of solidarity and cohesion, and the latter conceived their visions of unity and belonging based on those feelings. However, the findings reveal that these visions did not coalesce with the “grand” or “official” narratives of unification and inclusion, given the audience’s strong sense of togetherness and attachment to their state of origin and community rather than to the country and the nation. Such findings are important as they provide insights into the potential role that popular music of Malaysia’s indigenous ethnic communities can play in the complex and never-ending process of achieving a national sense of unity, belonging and identity in Malaysia.